Hak Atas Kebebasan Beragama Sebagai Non Derogable Rights Dalam Perspektif Konstitusi Indonesia - Probo Pribadi S.M (Suara Edukasi Hukum, 2025)
The right to freedom of religion is one of the most fundamental human rights and cannot be diminished under any circumstances, including during emergencies. This article discusses the strategic position of the right in the Indonesian constitution as well as the actual challenges in its implementation. This research uses a normative legal approach by analyzing laws and regulations, legal theories, international comparative practices, and Constitutional Court decisions. The results of the study show that the constitutional guarantees in Articles 28E, 28I, and 29 of the 1945 Constitution, which are strengthened through the ratification of the ICCPR, have not been fully implemented evenly. There are still obstacles in the form of exclusive regulations, discriminatory bureaucratic practices, and social pressure on minority groups. Therefore, concrete steps are needed from the state to provide inclusive legal protection, in line with the spirit of the constitution and the values of Pancasila. This study is expected to be an academic contribution in strengthening the guarantee of freedom of religion in Indonesia in a sustainable and equitable manner